2006
DOI: 10.1186/1471-2458-6-67
|View full text |Cite
|
Sign up to set email alerts
|

Trends in drinking habits among adolescents in the Baltic countries over the period of transition: HBSC survey results, 1993–2002

Abstract: Background: The Baltic countries -Estonia, Latvia, and Lithuania -are considered to be an example of regional homogeneity over the period of transition. The World Health Organization cross-national study on Health Behavior in School-aged Children (HBSC) allows a comparison and time trends analysis of behavioral patterns among adolescents in this region. The aim of this study was to estimate the prevalence and trends of alcohol consumption and drunkenness among adolescents of Estonia, Latvia, and Lithuania in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 15 publications
5
32
0
2
Order By: Relevance
“…Pastebėta, kad vaikinai, lyginant su merginomis, suvartoja didesnį alkoholinių gėrimų kiekį, o dėl agresyvios rinkodaros politikos ir vis jaunėjančio vartojančiųjų amžiaus vaikinų ir merginų alkoholinių gėrimų vartojimo įpročių skirtumai ženkliai sumažėjo daugelyje šalių (4). Mergaičių alkoholio vartojimo pokyčiai itin akivaizdūs Centrinėje ir Rytų Europoje, t. y. tuose regionuose, kuriuose vyko reikšmingi ekonominiai pokyčiai ir pradėta agresyvi alkoholio rinkodara (4,12,17,18,27).…”
Section: Mergaitės Berniukaiunclassified
See 1 more Smart Citation
“…Pastebėta, kad vaikinai, lyginant su merginomis, suvartoja didesnį alkoholinių gėrimų kiekį, o dėl agresyvios rinkodaros politikos ir vis jaunėjančio vartojančiųjų amžiaus vaikinų ir merginų alkoholinių gėrimų vartojimo įpročių skirtumai ženkliai sumažėjo daugelyje šalių (4). Mergaičių alkoholio vartojimo pokyčiai itin akivaizdūs Centrinėje ir Rytų Europoje, t. y. tuose regionuose, kuriuose vyko reikšmingi ekonominiai pokyčiai ir pradėta agresyvi alkoholio rinkodara (4,12,17,18,27).…”
Section: Mergaitės Berniukaiunclassified
“…Pereinamasis laikotarpis į rinkos ekonomiką, vykstant žiniasklaidos ir prekybos globalizacijai, turi vis didesnę reikšmę Centrinės ir Rytų Europos šalių jaunų žmonių gyvensenos sampratai, elgesiui ir pasirinkimams (10)(11)(12). Šiam laikmečiui būdingų pokyčių neišvengė ir Lietuvos jaunimas.…”
unclassified
“…Following processes inevitably influenced attitudes of children and youth regarding alcohol consumption and changed habits of its consumption. The results of two international surveys of schoolchildren lifestyle ("European School Survey on Alcohol and other Drugs -ESPAD" and "Health Behavior in School-Aged Children -HBSC") demonstrated only increasing extent of alcoholic consumption, and in the nearest future, a steady decrease cannot be expected as well (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous investigations have been conducted worldwide to describe alcohol abuse by youth [1][2][3][10][11][12][13][14][15], the data from our country are still insufficient. The aim of the present study was to investigate the prevalence and predictors of alcohol consumption among adolescents in one town in Central Serbia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies focusing on this issue revealed that the causes of excessive alcohol consumption usually comprise not only psychological and demographic factors, but also different social and economic factors [2,4,9,10], suggesting that the scope and nature of this problem may differ among countries.…”
Section: Introductionmentioning
confidence: 99%